Impact of Vaccine Manufacturing Announcement During Pandemic on The Stock Market Reaction of Pharmaceutical Companies - Cellina Trishana (Journal of Social Science, 2022)
The objective of this research is to identify whether there is a significant difference in the market reaction shown by the abnormal return and trading volume activity before and after the vaccine manufacturing announcement conducted by listed pharmaceutical companies around the world. The sample used in this research is listed pharmaceutical companies that conducted a vaccine manufacturing announcement during a pandemic, and the data collected is secondary data. This research uses the event study as its methodology with 3 event windows, which are one month before and after the announcement, ten days before and after the announcement, and five days before and after the announcement. The analysis of the normality test and paired difference test is conducted using the Wilcoxon Signed Rank Test with a significance level of 0.05. The result shows that there is no significant difference in both abnormal return and trading volume activity of the listed pharmaceutical companies before and after the vaccine manufacturing announcement. From this research, it can be concluded that the vaccine manufacturing announcement during a pandemic does not have a significant effect on the market reaction. To extend and further test the market reaction of pharmaceutical companies, future research could be done by exploring more on the effect of health-related news on all pharmaceutical companies, and the variables tested could be expanded